Casebook on European Order for Payment Procedure and European Small Claims Procedure - Ivanc, Tjaša; Rijavec, Vesna; Zahrastnik, Kristjan (2022)
Publication Case studies on European order for payment procedure and European small claims procedure was created as part of the Train to Enforce project and is the result of the collaboration of eight faculties of law across Europe. The publication contains numerous case studies focusing on European order for payment procedure (Regulation No. 1896/2006) and European small claims procedure (Regulation No. 861/2007). Case studies focus on both the practical and theoretical aspects of the European order for payment procedure and European small claims procedure. They will promote self-learning on cross-border debt collection in the EU.
Keywords: case study; European order for payment procedure; European small claims procedure,; cross-border debt colletion; civil and commercial matters